(3GdUdGI hGdhaG aj GdUdGI Ydi GdeUWais - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3jbhd YHO GdQMef Hf CHj HcQ GdSjhWj GdTGaYjGdMeO ddg Ydi fYeGFg GdhGaQIgPG cJGH JVef Mce GdUdGI Ydi GdfHjef GdCMGOjK GdhGQOI SejJg HGdUdGI hGdhaG aj GdUdGI Ydi GdeUWais
(3BNQgG (B:s
(3eDefGf SdjeGf hPh GdbQfjf YdjgeG GdSdGe hcGaQGf GdfeQhO GHf cfYGf hHNJ fUQ hgPG BNQ eG CQOJ PcQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs